Changes in Public Perception of Juvenile Delinquency (Case Study in Mulyoagung Village) - Maulana, Ali Akhbar; Kumalasari, Luluk Dwi (ARISTO, 2026)
This study aims to identify the shifting forms of community perceptions of juvenile delinquency over time (case study in Mulyoagung Village). Juvenile delinquency according to the community is a social problem that is considered as intimidation equivalent to social deviation, but over time the perception of the community has changed the way of thinking about juvenile delinquency. This research was conducted using a purposive sampling method with a qualitative research approach. The data collection methods used were observation, interviews, and documentation involving the community and adolescents as research subjects. The results of this study identify that there is a change in people's perceptions of juvenile delinquency, where according to the community, juvenile delinquency is currently very concerning due to various factors such as environmental factors, family factors, social factors, and friendship factors. The community responds to juvenile delinquency in different ways, based on research this is seen with the difference in age among the community. This has a negative impact if the community ignores the existence of juvenile delinquency in the social environment, therefore the community plays an important role in maintaining social stability. Keywords: Perception Change; Juvenile Delinquency; Society;